COMPARATIVE ADVANTAGE IN HONEY TRADE AMONG THE TOP EXPORTING COUNTRIES IN THE WORLD - Agatha POPESCU; Toma Adrian DINU; Elena STOIAN; Valentin ŞERBAN (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The paper aimed to analyze the competitiveness of top 16 honey exporting countries in the world in the period 2018-2021 using World Bank data, based on the specific indicators Revealed Comparative Advantage (RCA), Revealed Symmetric Comparative Advantage (RSCA), Comparative Export Performance Index (CEP) and Trade Balance Index (TBI). The results showed that in 2021, New Zealand, Argentina, Ukraine, Greece, Hungary, Romania, Brazil, India, Spain, Vietnam, Poland and Mexico had a comparative advantage, while EU, China and Germany have a comparative disadvantage in the international honey market. A strong comparative advantage belongs to New Zealand, Argentina, Ukraine, Hungary and Romania, and partially to Greece, a moderate comparative advantage belongs to Brazil, India, Spain, Mexico, Vietnam and Greece in specific years, a weak comparative advantage belongs to Poland, Vietnam, China and Spain in specific years, and finally, China, EU and Germany are disadvantaged. The highest RSCA is characteristic to New Zealand, Argentina, Ukraine, Greece, Hungary, Romania and Brazil. New Zealand has the highest CEP against EU, China, Germany, and the smallest CEP versus Brazil, Romania, Hungary, Greece and mainly Ukraine. New Zealand, Argentina, Brazil, Ukraine, Hungary, Mexico, followed by India and Vietnam have a high TBI being net exporting countries. EU, Germany, Poland had a negative TBI, reflecting that they are net importers and also Greece in 2018. As any country desires to be more competitive, exports and imports have to be kept under control, larger amounts to be available to be sold at the best price and the geographic area of influence to be extended looking for new trade partners.